STUDENTS’ PERCEPTIONS AND USE OF YOUTUBE FOR IMPROVING ENGLISH SPEAKING SKILLS AMONG ENGLISH EDUCATION STUDENTS AT UINSU - Dhea Salsabila; Harshanda Rafika Putriana; Didik Santoso; Nadia Wulandari; Ajrul Khair (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT In the digital era, technology plays an important role in supporting English language learning, particularly in developing speaking skills in EFL (English as a Foreign Language) contexts, where students have limited exposure to authentic communication. This study aimed to investigate students' perceptions and their use of YouTube in improving English speaking skills among students of the English Education Study Program at Universitas Islam Negeri Sumatera Utara (UINSU). The study employed a quantitative descriptive survey design involving 50 students from the 2023 cohort selected through purposive sampling. Data were collected using a Likert-scale questionnaire distributed via Google Forms and analyzed using descriptive statistics and the Pearson Product-Moment Correlation test. The findings revealed that students had positive perceptions of YouTube (M = 4.22), frequently used it for speaking practice (M = 4.08), and perceived improvements in their speaking skills (M = 3.96). Correlation analysis indicated significant positive relationships between students' perceptions and speaking skill improvement (r = 0.648; p < 0.001), as well as between YouTube use and speaking skill improvement (r = 0.732; p < 0.001). These findings provide additional empirical evidence on the relationship between students' perceptions, YouTube use, and speaking skill development in higher education EFL contexts. The study also highlights the potential of integrating YouTube as a complementary digital learning medium to enhance students' oral communication competence. ABSTRAK Pada era digital, teknologi memegang peranan penting dalam mendukung pembelajaran bahasa Inggris, khususnya pengembangan keterampilan berbicara pada konteks EFL (English as a Foreign Language), ketika mahasiswa memiliki keterbatasan paparan terhadap komunikasi autentik. Penelitian ini bertujuan menginvestigasi persepsi mahasiswa dan penggunaan YouTube dalam meningkatkan keterampilan berbicara bahasa Inggris pada mahasiswa Program Studi Pendidikan Bahasa Inggris Universitas Islam Negeri Sumatera Utara (UINSU). Penelitian menggunakan desain survei deskriptif kuantitatif dengan sampel 50 mahasiswa angkatan 2023 yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan kuesioner skala Likert melalui Google Forms dan dianalisis menggunakan statistik deskriptif serta Korelasi Pearson Product-Moment. Hasil penelitian menunjukkan bahwa mahasiswa memiliki persepsi positif terhadap YouTube (M = 4,22), sering menggunakannya untuk latihan berbicara (M = 4,08), dan merasakan peningkatan keterampilan berbicara (M = 3,96). Analisis korelasi menunjukkan hubungan positif yang signifikan antara persepsi mahasiswa dan peningkatan keterampilan berbicara (r = 0,648; p < 0,001), serta antara penggunaan YouTube dan peningkatan keterampilan berbicara (r = 0,732; p < 0,001). Temuan ini memperkaya bukti empiris mengenai keterkaitan persepsi mahasiswa, penggunaan YouTube, dan peningkatan keterampilan berbicara pada konteks EFL di perguruan tinggi. Implikasi penelitian menegaskan bahwa YouTube layak diintegrasikan sebagai media pendukung pembelajaran berbicara untuk meningkatkan kompetensi komunikasi lisan mahasiswa.